A INCLUSÃO DO OUTRO AUTISTA ENQUANTO UM PRINCÍPIO DE JUSTIÇA SOCIAL NOS CONSELHOS DELIBERALITIVOS NACIONAIS DE SAÚDE, EDUCAÇÃO E ASSISTÊNCIA SOCIAL NO BRASIL (2019-2022) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This study addresses the following problem: Have the National Deliberative Councils for Health, Education, and Social Assistance contributed to the establishment and direction of the national policy for the protection of autistic individuals, from the perspective of "inclusion of the other" as a principle of social justice? To answer this question, the research aims to analyze how the National Deliberative Councils for Health, Education, and Social Assistance, institutionalized within the public sphere in Brazil, have contributed to the national policy for the protection of individuals with autism spectrum disorder from the perspective of "inclusion of the other" as a principle of social justice. The specific objectives are: to discuss how the scale and institutionalization of participation are treated by different perspectives of democratic theory that have emerged in the second half of the 20th century, particularly the deliberative democracy proposed by Jürgen Habermas; to explore the ethics of discourse and communicative action of civil society in the national deliberative councils, assuming the inclusion of autistic individuals as a principle of social justice; to analyze the sensitivity to the difference of autistic individuals within the institutionalized public sphere through the national deliberative councils for Health, Social Assistance, and Education in Brazil, from the perspective of civil society representatives associated with the defense of the autistic agenda in their respective spaces. This is a qualitative study with an interdisciplinary approach, using the critical historical method. Methodologically, the study is based on bibliographic, documentary, and field research, as demonstrated in the methodological chapter. Firstly, a literature review was conducted; secondly, the resolutions of the respective councils were analyzed for the past seven years to identify the research subjects and particularly the inclusion of the autistic agenda in their work; and finally, semi-structured interviews were conducted for the field phase. These interviews were transcribed and interpreted based on content analysis. Throughout the research, the interviews were inserted as an effort to objectify the material developed. As a result of this research, the following thesis was reached: the National Deliberative Councils for Health, Social Assistance, Education, and the Rights of Persons with Disabilities, as institutionalized deliberative democratic spaces within the public sphere in Brazil, have the potential to contribute to the direction of the national policy for the protection of autistic individuals from the perspective of "inclusion of the other" as a principle of social justice, when they are sensitive to differences and inserted in a context that moves away from an ultraneoliberal government policy, such as the one experienced in the last four years (2019-2022).
Keywords: Autismo; Democracia Deliberativa; Conselhos Deliberativos; Inclusão do outro; Justiça Social; Autism; Deliberative Democracy; Deliberative Councils; Inclusion of the Other; Social Justice; CNPQ::CIENCIAS SOCIAIS APLICADAS